Lignin ionic liquid composite material as well as preparation method and application thereof

By applying lignin and ionic liquid composite materials to the acidic oil field environment of carbon steel equipment, a stable and dense adsorption film is formed, which solves the problem of corrosion of carbon steel equipment in the acidic environment and achieves an efficient and safe corrosion inhibition effect.

CN119571332APending Publication Date: 2025-03-07LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411680396.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Carbon steel equipment is severely corroded in acidic oilfield environments, resulting in shortening the service life of the equipment and causing economic losses. Existing corrosion inhibitors such as inorganic salts and organic salts have risks of environmental pollution and toxicity.

Method used

The lignin and ionic liquid composite material are used as the corrosion inhibitor, and the coordination bond is formed through the hollow d orbit of lignin and Fe to form an adsorption film to improve the corrosion resistance of steel materials. The composite material is composed of ionic liquid produced by benzotriazole and tetrabutylphosphorus hydroxide and binds to lignin, and lignin is dissolved in the ionic liquid through π-π interaction.

Benefits of technology

It improves the stability and density of the adsorption film of composite materials on the metal surface, significantly improves the corrosion inhibition efficiency, reduces the direct contact between the corrosive media and the metal surface, extends the service life of the equipment, and avoids the environmental pollution and toxicity risks of traditional corrosion inhibitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571332A_ABST
    Figure CN119571332A_ABST
Patent Text Reader

Abstract

The invention provides a lignin ionic liquid composite material as well as a preparation method and application thereof. The lignin ionic liquid composite material is applied to the field of metal corrosion prevention. The preparation method of the composite material comprises the following steps: reacting benzotriazole with tetrabutylphosphorus hydroxide to obtain an ionic liquid, and dissolving lignin in the ionic liquid in a heating and stirring state to obtain the lignin ionic liquid composite material. Wherein the mass fraction of the lignin is 1-5% of the total mass of the lignin ionic liquid composite material. The lignin ionic liquid composite material provided by the invention is used as a corrosion inhibitor, and through the synergistic effect of lignin and ionic liquid, the stability and compactness of the composite material on a metal surface adsorption film are improved, so that the corrosion of metal is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of functional materials, and in particular to a lignin ionic liquid composite material, a preparation method and application thereof. Background Art

[0002] Carbon steel is widely used in the petrochemical industry because of its low cost, excellent welding performance, high strength and other advantages. In the process of oil extraction, carbon steel equipment is exposed to the acidic oil field environment for a long time, which causes serious corrosion to the carbon steel equipment, greatly shortening the service life of the carbon steel equipment, and causing huge economic losses. Therefore, it is necessary to take certain protective measures to reduce metal corrosion. Studies have found that the corrosion inhibitor method has become one of the effective means of metal protection because of its simple operation and high efficiency. And it has been widely used in the corrosion protection of steel equipment in acidic media.

[0003] At present, commonly used corrosion inhibitors include inorganic salt corrosion inhibitors, organic corrosion inhibitors, ionic liquids, etc. Inorganic salt corrosion inhibitors such as arsenic, chromate, nitrite, etc. are not only easy to cause environmental pollution during use, but also their high toxicity can easily endanger human health. Studies have found that the use of ionic liquids (ILs) as corrosion inhibitors has the characteristics of high efficiency, non-toxicity, and excellent thermal stability. Ionic liquids are liquid salts composed entirely of anions and cations at room temperature or low temperature (<100°C). And because of the designability of ionic liquid molecules, functional groups with antioxidant and anti-corrosion functions, polar elements such as N, P, and biomacromolecules can be introduced into them to make the prepared ionic liquids have excellent anti-corrosion properties.

[0004] Lignin, as a natural renewable polymer, contains a large number of aromatic ring structures and hydroxyl groups. The π electrons on the aromatic rings and the lone pair electrons in the hydroxyl groups can form coordination bonds with the empty d orbitals of Fe, forming a protective film on the metal surface. However, lignin is difficult to dissolve in traditional organic solvents, which limits its application. Summary of the invention

[0005] The present application provides a lignin ionic liquid composite material, a preparation method and application thereof, to solve the above-mentioned problems mentioned in the background technology.

[0006] On the one hand, the present application provides an application of a lignin ionic liquid composite material in a corrosion inhibitor, and the lignin ionic liquid composite material is applied in the field of metal corrosion protection. Since the lignin structure has a large number of carbonyl, phenolic hydroxyl functional groups and a conjugated aromatic structure with a high-density electron cloud, it can form a coordination bond with the empty d orbital of Fe, thereby forming an adsorption film on the steel surface to improve the corrosion resistance of the steel material. Through the synergistic effect of lignin and ionic liquid, they are adsorbed on the metal surface together, thereby improving the stability and density of the composite material adsorption film on the metal surface, and improving the corrosion inhibition efficiency.

[0007] On the other hand, the present application provides a method for preparing a lignin ionic liquid composite material, which is used to prepare the above-mentioned lignin ionic liquid composite material, and the preparation method comprises the following steps:

[0008] Preparation of ionic liquid: Add benzotriazole and tetrabutylphosphonium hydroxide into a reactor, and react for 18-28 hours under nitrogen protection and room temperature to obtain an ionic liquid;

[0009] Preparation of lignin ionic liquid composite material: Take ionic liquid and heat it to 50-200℃ under stirring, then add lignin to the ionic liquid, continue stirring until lignin is dissolved in the ionic liquid, and obtain lignin ionic liquid composite material. Lignin and ionic liquid can directly dissolve lignin in ionic liquid through π-π interaction between benzene rings, thereby effectively combining the effects of ionic liquid and lignin. Lignin contains a large number of active adsorption sites, and the adsorption layer formed by chemical bonds with atoms on the iron surface is larger than the adsorption layer of pure ionic liquid, thereby effectively reducing the direct contact area between the corrosive medium and the metal, and improving the corrosion inhibition performance of the metal.

[0010] Optionally, in the ionic liquid preparation step, the molar ratio of benzotriazole to tetrabutylphosphonium hydroxide is 1: 1. The added amounts of benzotriazole and tetrabutylphosphonium hydroxide are controlled to ensure that the reaction proceeds fully.

[0011] Optionally, in the step of preparing the lignin ionic liquid composite material, lignin is added to the ionic liquid, and the stirring and mixing is continued for 10-30 minutes to obtain the lignin ionic liquid composite material.

[0012] Optionally, in the ionic liquid preparation step, the reaction time is 20-25 hours.

[0013] Optionally, in the step of preparing the lignin-ionic liquid composite material, the dissolution temperature of lignin in the ionic liquid is 90-150°C.

[0014] Optionally, the ionic liquid preparation step further comprises:

[0015] After the reaction of benzotriazole and tetrabutylphosphonium hydroxide is completed, a reaction solution containing an ionic liquid is obtained, and the aqueous phase in the reaction solution containing the ionic liquid is extracted with an organic solvent, and then the organic solvent is removed by vacuum distillation, and finally anhydrous magnesium sulfate is added for drying, and a light yellow transparent oily liquid is obtained by filtration, which is the ionic liquid.

[0016] Optionally, the organic solvent is dichloromethane or chloroform.

[0017] On the other hand, the present application provides a lignin ionic liquid composite material, which is the above-mentioned lignin ionic liquid composite material used in the field of metal corrosion protection, or the lignin ionic liquid composite material obtained by the above-mentioned preparation method. The lignin ionic liquid composite material is composed of lignin and ionic liquid, and the mass fraction of lignin is 1-5% of the total mass of the lignin ionic liquid composite material.

[0018] Optionally, the ionic liquid has a structure shown in Formula 1:

[0019]

[0020] The lignin ionic liquid composite material, preparation method and application thereof provided in the present application realize the preparation and application of the lignin ionic liquid composite material, and have the following beneficial effects compared with the prior art:

[0021] (1) The present application uses a composite of lignin and ionic liquid as a corrosion inhibitor. Lignin contains a large number of active adsorption sites. The adsorption layer formed by chemical bonds with atoms on the iron surface is larger than the adsorption layer of pure ionic liquid. Through the synergistic effect of lignin and ionic liquid, they are adsorbed on the metal surface together, thereby improving the stability and density of the adsorption film of the composite material on the metal surface, making it more difficult for the corrosive medium to contact the metal surface, thereby improving the protective performance of the metal and improving the corrosion inhibition efficiency.

[0022] (2) Benzotriazole and tetrabutylphosphonium hydroxide generate an ionic liquid, and then lignin with an aromatic ring structure and BTA-P are reacted under heating and stirring. 4444 Ionic liquids directly dissolve lignin in BTA-P through the π-π interaction between benzene rings. 4444 In the process, lignin ionic liquid composites were synthesized to effectively combine the effects of ionic liquid and lignin. Lignin ionic liquid composites form a dense adsorption film through the π electrons on the aromatic ring and the N atoms on the benzotriazole molecule to form a stable coordination bond with the iron surface to inhibit the anode and cathode reactions of steel materials in acidic environments and improve the protective performance of metals.

[0023] (3) The preparation method of the lignin ionic liquid composite material provided in the present application has a simple process and easily controllable conditions, which is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following is a brief introduction to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0025] Figure 1 In order to study the molecular dynamics (MD) simulation of BTA-P 4444 , BTA-P 4444 -Computational simulation diagram of the adsorption film formed on the metal surface when Lig is used as a corrosion inhibitor; Figure 1 (a) is BTA-P 4444 Snapshot of a molecule adsorbed on the Fe(110) plane. Figure 1 (a1) is BTA-P 4444 A slice of the simulation box with thickness Figure 1 (b) is BTA-P 4444 -Snapshot of Lig molecule adsorbed on Fe(110) plane, Figure 1 (b1) is BTA-P 4444 -A slice of the Lig simulation box;

[0026] Figure 2 For water molecules in BTA-P 4444 , BTA-P 4444 -Lig density in adsorption film.

[0027] Figure 3 BTA-P 4444 , BTA-P 4444 -Computational simulation diagram of the adsorption behavior of Lig on the Fe(110) surface; Figure 3 (a) is BTA-P 4444 Adsorption behavior on metal surfaces; Figure 3 (b) is BTA-P 4444 -Lig adsorption behavior on metal surfaces. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work also fall within the scope of protection of the present application.

[0029] On the one hand, the present application provides an application of a lignin ionic liquid composite material in a corrosion inhibitor, and the lignin ionic liquid composite material is applied in the field of metal corrosion protection.

[0030] Specifically, the present application applies lignin ionic liquid composite materials to the field of corrosion protection of metal surfaces, and metals include metals such as iron, copper, aluminum, nickel and their alloys. Preferably, the lignin ionic liquid composite materials provided by the present application are used as corrosion inhibitors on the surface of steel materials, greatly reducing the corrosion of steel materials in acidic environments. Ionic liquids have the characteristics of high efficiency, non-toxicity and excellent thermal stability as corrosion inhibitors. They can be adsorbed on the metal surface to form an adsorption film, blocking the direct contact between the metal surface and the corrosive medium, playing a good protective role, and thus avoiding the corrosion of the metal surface by the corrosive medium. Lignin, as a natural renewable polymer, has a large number of carbonyl, phenolic hydroxyl functional groups and a conjugated aromatic structure with a high-density electron cloud in the structure, so that it can form a coordination bond with the empty d orbital of Fe, thereby forming an adsorption film on the steel surface to improve the corrosion resistance of the steel material.

[0031] When used as a corrosion inhibitor, the lignin ionic liquid composite material is added to the corrosive medium and stirred to be uniformly dispersed. The amount of the lignin ionic liquid composite material added to the corrosive medium is 0.01wt.%-0.06wt.%, preferably 0.01wt.%-0.04wt.%.

[0032] The present application combines lignin with ionic liquid as a corrosion inhibitor, and through the synergistic effect of lignin and ionic liquid, they are jointly adsorbed on the metal surface, thereby improving the stability and density of the adsorption film of the composite material on the metal surface, making it more difficult for the corrosive medium to contact the metal surface, thereby improving the protective performance of the metal.

[0033] On the other hand, the present application provides a method for preparing a lignin ionic liquid composite material, which is used to prepare the above-mentioned lignin ionic liquid composite material, and the preparation method comprises the following steps:

[0034] Preparation of ionic liquid: Add benzotriazole and tetrabutylphosphonium hydroxide into a reactor, and react for 18-28 hours under nitrogen protection and room temperature to obtain an ionic liquid;

[0035] Preparation of lignin ionic liquid composite material: Take ionic liquid and heat it to 50-200° C., add lignin to the ionic liquid under stirring, and continue stirring until the lignin is dissolved in the ionic liquid to obtain the lignin ionic liquid composite material.

[0036] Specifically, in the ionic liquid preparation step, benzotriazole and tetrabutylphosphonium hydroxide are reacted to obtain an ionic liquid named BTA-P 4444 The ionic liquid is then heated and mixed with lignin under stirring to dissolve the lignin in the ionic liquid to obtain a lignin ionic liquid composite material named BTA-P 4444-Lig. Lignin has a conjugated aromatic structure with a high-density electron cloud, and the benzotriazole in the ionic liquid contains a benzene ring. Lignin and the ionic liquid can directly dissolve lignin in the ionic liquid through the π-π interaction between the benzene rings, thereby effectively combining the effects of the ionic liquid and lignin. The dissolution temperature of lignin in the ionic liquid is 50-200°C, which is more conducive to the rapid dissolution of lignin.

[0037] The present application realizes the preparation of lignin ionic liquid composite material through the above scheme, by generating ionic liquid from benzotriazole and tetrabutylphosphonium hydroxide, and then dissolving lignin in the ionic liquid under heating and stirring to synthesize lignin ionic liquid composite material, and effectively combining the effects of ionic liquid and lignin. Lignin ionic liquid composite material can form a stable and dense adsorption film on the metal surface, avoiding direct contact between the metal matrix and the corrosive medium, thereby playing a good protective role and improving the corrosion inhibition efficiency of the metal matrix.

[0038] Furthermore, the preparation method of the lignin ionic liquid composite material provided in the present application has a simple process and easily controllable conditions, which is conducive to large-scale production.

[0039] Optionally, in the ionic liquid preparation step, the molar ratio of benzotriazole to tetrabutylphosphonium hydroxide is 1:1.

[0040] Optionally, in the step of preparing the lignin ionic liquid composite material, lignin is added to the ionic liquid, and the stirring and mixing is continued for 10-30 minutes to obtain the lignin ionic liquid composite material.

[0041] Specifically, the mixture is stirred for 10-30 minutes until the mixed liquid of the ionic liquid and lignin is clear and transparent. The method of adding lignin to the ionic liquid is not limited, and the stirring speed during the dissolution of lignin is not limited. The stirring speed familiar to those skilled in the art can be used.

[0042] Preferably, the mixing and dissolving time is 15-25 min, more preferably 20 min.

[0043] Optionally, in the ionic liquid preparation step, the reaction time is 20-25 hours. More preferably, the reaction time is 24 hours.

[0044] Optionally, in the step of preparing the lignin-ionic liquid composite material, the dissolution temperature of lignin in the ionic liquid is 90-150°C, preferably 95-120°C, and more preferably 100°C.

[0045] Optionally, the ionic liquid preparation step further comprises:

[0046] After the reaction of benzotriazole and tetrabutylphosphonium hydroxide is completed, a reaction solution containing an ionic liquid is obtained, and the aqueous phase in the reaction solution containing the ionic liquid is extracted with an organic solvent, and then the organic solvent is removed by vacuum distillation, and finally anhydrous magnesium sulfate is added for drying, and a light yellow transparent oily liquid is obtained by filtration, which is the ionic liquid.

[0047] Optionally, the organic solvent is dichloromethane or chloroform.

[0048] Specifically, after the reaction of benzotriazole and tetrabutylphosphonium hydroxide is completed, a reaction solution containing an ionic liquid is obtained, which is further purified to obtain an ionic liquid. An organic solvent is added to the reaction solution containing the ionic liquid for extraction, and the ionic liquid is dissolved in the organic solvent. Therefore, after the organic solvent is added, the organic solvent-ionic liquid and the water layer are separated to obtain an organic phase and an aqueous phase. After standing, the aqueous phase is separated, and the aqueous phase in the ionic liquid is removed by extraction. The organic solvent is then evaporated by vacuum distillation, and finally anhydrous magnesium sulfate is added and dried for 8-24 hours to further remove the moisture in the ionic liquid. After drying, the anhydrous magnesium sulfate is removed by filtration to obtain an ionic liquid, namely BTA-P 4444 . The purpose of purifying ionic liquids is achieved.

[0049] The organic solvent is selected from dichloromethane or chloroform. More preferably, the organic solvent is dichloromethane, which is more stable than chloroform.

[0050] The amount of anhydrous magnesium sulfate used is: 10-20g of anhydrous magnesium sulfate is added for every 100g of ionic liquid. The process of removing the organic solvent by vacuum distillation is a common and mature impurity removal method in the art. Those skilled in the art are capable of adjusting the operating parameters in the vacuum distillation according to the actual solvent to be distilled, and the conditions of the vacuum distillation are not limited here.

[0051] On the other hand, the present application provides a lignin ionic liquid composite material, which is the above-mentioned lignin ionic liquid composite material used in the field of metal corrosion protection, or the lignin ionic liquid composite material obtained by the above-mentioned preparation method. The lignin ionic liquid composite material is composed of lignin and ionic liquid, and the mass fraction of lignin is 1-5% of the total mass of the lignin ionic liquid composite material.

[0052] Optionally, the ionic liquid has a structure shown in Formula 1:

[0053]

[0054] Specifically, the ionic liquid BTA-P provided in this application 4444Obtained by the reaction of benzotriazole and tetrabutylphosphonium hydroxide, the introduction of benzotriazole groups is beneficial to improving the adsorption stability of the composite material on the metal surface, thereby improving the stability of the adsorption film, and helping to improve the corrosion inhibition efficiency of the composite material as a metal corrosion inhibitor. At the same time, the lignin structure has a large number of carbonyl, phenolic hydroxyl functional groups and a conjugated aromatic structure with a high-density electron cloud, which enables it to form a coordination bond with the empty d orbital of Fe, thereby forming an adsorption film on the steel surface to improve the corrosion resistance of the steel material and further improve the corrosion inhibition performance of the composite material. Based on lignin with an aromatic ring structure and BTA-P 4444 It can directly dissolve lignin in BTA-P through the π-π interaction between benzene rings. 4444 In this way, the effects of ionic liquid and lignin are effectively combined. Through the synergistic effect of lignin and tetrabutylphosphonium hydroxide benzotriazole ionic liquid, the lignin ionic liquid composite corrosion inhibitor can be effectively adsorbed on the steel surface, and the π electrons on the aromatic ring and the N atoms on the benzotriazole molecule form a stable coordination bond with the iron surface, thereby forming a dense adsorption film to inhibit the anodic and cathodic reactions of the steel material in an acidic environment and improve the protective performance of the metal.

[0055] Compared with pure ionic liquids, the combination of lignin and ionic liquids contains a large number of active functional groups such as hydroxyl, carboxyl, and carbonyl, that is, a large number of active adsorption sites. Therefore, the adsorption layer formed by the lignin ionic liquid composite material containing rich active elements and functional groups through chemical bonds with the atoms on the iron surface is larger than the adsorption layer of pure ionic liquids, thereby effectively reducing the direct contact area between the corrosive medium and the metal and improving the corrosion inhibition performance of the metal.

[0056] At the same time, the lignin structure itself has a large conjugated aromatic structure and has excellent thermal stability at high temperatures, which helps the lignin ionic liquid composites to be applied in more operating conditions with higher temperatures.

[0057] Example 1

[0058] A method for preparing a lignin ionic liquid composite material comprises the following steps:

[0059] (1) Preparation of ionic liquid: Take equimolar amounts of benzotriazole and tetrabutylphosphonium hydroxide and add them to a reactor. React for 18 hours under nitrogen protection and room temperature. After the reaction is completed, a reaction solution containing ionic liquid is obtained. Dichloromethane is added to the reaction solution containing ionic liquid for extraction. Dichloromethane-ionic liquid and water are separated to obtain dichloromethane phase and water phase. The water phase is removed after standing. Dichloromethane is then evaporated by vacuum distillation. Finally, anhydrous magnesium sulfate is added and dried for 8 hours to further remove moisture from the ionic liquid. After drying, anhydrous magnesium sulfate is removed by filtration to obtain an ionic liquid.

[0060] (2) Preparation of lignin ionic liquid composite material: Take an ionic liquid and heat it to 50°C. Add lignin to the ionic liquid under stirring, and continue stirring until the lignin is dissolved in the ionic liquid to obtain a lignin ionic liquid composite material. The mass fraction of lignin is 1% of the total mass of the lignin ionic liquid composite material.

[0061] Example 2

[0062] A method for preparing a lignin ionic liquid composite material comprises the following steps:

[0063] (1) Preparation of ionic liquid: Take equimolar amounts of benzotriazole and tetrabutylphosphonium hydroxide and add them to a reactor. React under nitrogen protection and room temperature for 24 hours. After the reaction is completed, a reaction solution containing ionic liquid is obtained. Dichloromethane is added to the reaction solution containing ionic liquid for extraction. Dichloromethane-ionic liquid and water are separated to obtain dichloromethane phase and water phase. The water phase is removed after standing. Dichloromethane is then evaporated by vacuum distillation. Finally, anhydrous magnesium sulfate is added and dried for 16 hours to further remove moisture from the ionic liquid. After drying, anhydrous magnesium sulfate is removed by filtration to obtain an ionic liquid.

[0064] (2) Preparation of lignin ionic liquid composite material: Take ionic liquid and heat it to 100°C. Under stirring, add lignin to the ionic liquid and continue stirring until the lignin is dissolved in the ionic liquid to obtain a lignin ionic liquid composite material. The mass fraction of lignin is 3% of the total mass of the lignin ionic liquid composite material.

[0065] Example 3

[0066] A method for preparing a lignin ionic liquid composite material comprises the following steps:

[0067] (1) Preparation of ionic liquid: Take equimolar amounts of benzotriazole and tetrabutylphosphonium hydroxide and add them to a reactor. React under nitrogen protection and room temperature for 28 hours. After the reaction is completed, a reaction solution containing ionic liquid is obtained. Dichloromethane is added to the reaction solution containing ionic liquid for extraction. Dichloromethane-ionic liquid and water are separated to obtain dichloromethane phase and water phase. The water phase is removed after standing. Dichloromethane is then evaporated by vacuum distillation. Finally, anhydrous magnesium sulfate is added and dried for 24 hours to further remove the water in the ionic liquid. After drying, anhydrous magnesium sulfate is removed by filtration to obtain an ionic liquid. (2) Preparation of lignin ionic liquid composite material: Take an ionic liquid and heat it to 200°C. Under stirring, add lignin to the ionic liquid and continue stirring until the lignin is dissolved in the ionic liquid to obtain a lignin ionic liquid composite material. The mass fraction of lignin is 5% of the total mass of the lignin ionic liquid composite material.

[0068] Experimental Example 1

[0069] Ionic Liquid BTA-P 4444 Structural characterization

[0070] The ionic liquids obtained by the technical solutions provided in Examples 1 to 3 were subjected to nuclear magnetic resonance and mass spectrometry analysis. The results showed that Examples 1-3 all achieved the preparation of ionic liquids, wherein the characterization data of Example 2 are as follows:

[0071] The results are as follows: 1 H NMR (400MHz, CDCl3) δ (ppm), 7.76 (d, J = 8.0Hz, 2H), 6.98 (dd, J = 8.0, 4.0Hz, 2H), 1.78 (t, J = 16.0Hz, 8H), 1.38-1.18 (m, 16H), 0.85 (t, J = 8.0Hz, 12H). 13 CNMR(100MHz, CDCl3)δ(ppm),145.44,120.18,116.23,23.74,23.59,23.40,23.35,18.32,17.85,13.32. 31 PNMR (162MHz,CDCl3)δ(ppm),30.06(s)cation[C 16 H 36 P] + Mass spectrometry calculated value: 255.2929, found value: 255.2922, anion [C6H4N3] - Mass spectrum calculated value: 118.2200, measured value: 118.2194.

[0072] In Examples 1 to 3, BTA-P was synthesized. 4444 The ionic liquid is then dissolved in the ionic liquid under heating to obtain a lignin ionic liquid composite material that is a yellow transparent oily liquid, thereby achieving the preparation of the lignin ionic liquid composite material.

[0073] Example 4

[0074] Application of lignin-ionic liquid composites as corrosion inhibitors

[0075] In this application, the lignin ionic liquid composite material (BTA-P 4444 -Lig) is used as a corrosion inhibitor for metal surface corrosion inhibition, preferably in the acidic environment of oil field exploitation. In this embodiment, the BTA-P provided in Example 2 4444-Lig as an example, a 5 mol / L HCl solution was used as a corrosion medium to simulate the acidic environment of an oil field to detect the corrosion inhibition performance of the lignin ionic liquid composite material provided in the present application as a corrosion inhibitor at different concentrations (0.00wt.%, 0.01wt.%, 0.02wt.%, 0.03wt.%, 0.04wt.%) and different temperatures (room temperature, 30°C, 40°C, 50°C).

[0076] 0 g, 0.025 g, 0.050 g, 0.075 g, and 0.100 g of lignin ionic liquid composite corrosion inhibitor were respectively added into 227.3 mL of 5 mol / L HCl corrosion medium to obtain mixed solutions with concentrations of 0.00 wt.%, 0.01 wt.%, 0.02 wt.%, 0.03 wt.%, and 0.04 wt.% of lignin ionic liquid composite corrosion inhibitor.

[0077] Experimental Example 2.1

[0078] The weight loss method was used to calculate the corrosion inhibition efficiency of Q235 steel by comparing the weight loss of Q235 steel with and without corrosion inhibitor. At room temperature, 5 pieces of Q235 steel were completely immersed in the mixed solution containing different concentrations of lignin ionic liquid composite corrosion inhibitor provided in Example 4 above for 6 hours, and their corrosion inhibition performance (corrosion inhibition rate V, corrosion inhibition efficiency) was studied. The results are shown in Table 1.

[0079] Table 1 Different concentrations of BTA-P 4444 Corrosion inhibition performance of -Lig inhibitor in 5 mol / L HCl at room temperature

[0080]

[0081] Experimental Example 2.2

[0082] At 30°C, 5 pieces of Q235 steel were completely immersed in the mixed solution containing different concentrations of lignin ionic liquid composite corrosion inhibitor provided in the above Example 4 for 6 hours, and the corrosion inhibition performance (corrosion inhibition rate, corrosion inhibition efficiency) thereof was studied. The results are shown in Table 2.

[0083] Table 2 Different concentrations of BTA-P 4444 Corrosion inhibition performance of -Lig inhibitor in 5 mol / L HCl at 30°C

[0084]

[0085] Experimental Example 2.3

[0086] At 40°C, 5 pieces of Q235 steel were completely immersed in the mixed solution containing different concentrations of lignin ionic liquid composite corrosion inhibitor provided in the above Example 4 for 6 hours, and the corrosion inhibition performance (corrosion inhibition rate, corrosion inhibition efficiency) thereof was studied. The results are shown in Table 3.

[0087] Table 3 Different concentrations of BTA-P 4444 Corrosion inhibition performance of -Lig inhibitor in 5 mol / L HCl at 40°C

[0088]

[0089] Experimental Example 2.4

[0090] At 50°C, 5 pieces of Q235 steel were completely immersed in the mixed solution containing different concentrations of lignin ionic liquid composite corrosion inhibitor provided in the above Example 4 for 6 hours, and the corrosion inhibition performance (corrosion inhibition rate, corrosion inhibition efficiency) thereof was studied. The results are shown in Table 4.

[0091] Table 4 Different concentrations of BTA-P 4444 Corrosion inhibition performance of -Lig inhibitor in 5 mol / L HCl at 50°C

[0092]

[0093] Observe the data in Tables 1-4. Compared with blank hydrochloric acid (concentration of 0wt.%), the addition of lignin ionic liquid composite corrosion inhibitor greatly inhibits the corrosion rate of Q235 steel in 5mol / L HCl solution. In a 5mol / L HCl solution at room temperature and 30°C, the corrosion rate of Q235 steel is reduced by about 10 times in a corrosion solution with an inhibitor addition amount of 0.04wt.%. At a temperature of 40°C, the corrosion rate is reduced by about 4 times, and at a temperature of 50°C, the corrosion rate is reduced by almost 2.5 times. Observe the data in Tables 1-4, and it can be clearly seen that as the concentration of the added lignin ionic liquid composite corrosion inhibitor gradually increases, the corrosion inhibition rate gradually increases. It is shown that the lignin ionic liquid composite corrosion inhibitor provided in this application has excellent corrosion inhibition performance, and as a corrosion inhibitor, it can significantly reduce the corrosion of steel materials in the acidic environment of oil fields.

[0094] Experimental Example 3

[0095] The electrochemical behavior of the lignin ionic liquid composite corrosion inhibitor was detected by electrochemical impedance spectroscopy (EIS).

[0096] Mixed solutions of 0.00wt.%, 0.01wt.%, 0.02wt.%, 0.03wt.% and 0.04wt.% of the lignin ionic liquid composite corrosion inhibitor shown in Example 4 were taken respectively, and electrochemical impedance spectroscopy (EIS) was used to detect the electrochemical behavior of the lignin ionic liquid composite as a corrosion inhibitor.

[0097] Test conditions: using the traditional three-electrode system. The surface exposure area is 1cm 2 Q235 steel was used as the working electrode, saturated calomel electrode as the reference electrode, and platinum electrode as the auxiliary electrode. The measurement frequency range of electrochemical impedance spectroscopy (EIS) was 10 -2 -10 5 Hz, AC amplitude of 10mV, after the open circuit potential is stabilized, the corrosion inhibition performance of Q235 steel immersed in 5mol / L HCl solution containing different concentrations of lignin ionic liquid composite corrosion inhibitor is tested at room temperature. The test results are shown in Table 5.

[0098] Table 5 Electrochemical impedance spectroscopy test of different concentrations of lignin ionic liquid composite corrosion inhibitor in 5 mol / L HCl solution at room temperature

[0099]

[0100] Experimental Example 4

[0101] The electrochemical behavior of the lignin ionic liquid composite corrosion inhibitor was detected by potentiodynamic polarization curve. Mixed solutions of 0.00wt.%, 0.01wt.%, 0.02wt.%, 0.03wt.%, and 0.04wt.% of the lignin ionic liquid composite corrosion inhibitor concentrations shown in Example 4 were taken respectively, and the electrochemical behavior of the lignin ionic liquid composite as a corrosion inhibitor was detected by potentiodynamic polarization curve.

[0102] Test conditions: The corrosion inhibition performance of Q235 steel immersed in 5 mol / L HCl solution containing different concentrations of lignin ionic liquid composite corrosion inhibitor was measured at room temperature at a scan rate of 1 mV / s in a dynamic potential range of ±600 mV relative to the open circuit potential. The test results are shown in Table 6.

[0103] Table 6 Potentiodynamic polarization curves of lignin ionic liquid composite corrosion inhibitors with different concentrations in 5 mol / L HCl solution at room temperature

[0104]

[0105] Observing the data in Tables 5 and 6, compared with blank hydrochloric acid, the addition of lignin ionic liquid composite corrosion inhibitor greatly inhibited the corrosion of Q235 steel in 5 mol / L HCl solution, and with the increase of the concentration of lignin ionic liquid composite corrosion inhibitor, the corrosion inhibition efficiency (η) and charge transfer resistance (R ct ), double layer capacitance (C dl ) increased, and the corrosion current density (I corr ) decreases, the polarization resistance value (R p ) increases. In a 5 mol / L HCl solution at room temperature, when the lignin ionic liquid composite corrosion inhibitor is added in an amount of 0.04 wt.% in a mixed solution, the measured R ct Up to 5133.0Ω / cm 2 , R p Up to 5241.6Ω / cm 2 ,I corr Reduced to 6.046μm / cm 2 . R ct , R p It is obviously greater than the R of the corrosion solution with the addition amount of lignin ionic liquid composite material being 0.01wt.%, 0.02wt.%, and 0.03wt.%. ct , R p I corr It is obviously lower than the I of the corrosion solution with the addition amount of lignin ionic liquid composite material being 0.01wt.%, 0.02wt.%, and 0.03wt.%. corr And from Table 5, we can see that C dl Reduced to 5.43×10 -7 μF / cm 2 It is obviously less than the corrosion solution with the addition amount of lignin ionic liquid composite material of 0.01wt.%, 0.02wt.%, and 0.03wt.%. This is because the corrosion solution of lignin ionic liquid composite material with a concentration of 0.04wt.% can be adsorbed on the surface of Q235 steel in large quantities compared with the corrosion solution with a smaller concentration, forming a stable adsorption layer. The more stable the adsorption film formed, the denser the adsorption film at the metal interface, the smaller the double layer distance, and the greater the capacitance. The double layer capacitance is significantly reduced at high concentrations, indicating that more corrosion inhibitor molecules are easily adsorbed to the surface of the electrode, making the corrosion inhibitor adsorption layer denser, making it difficult for the corrosive medium to approach the metal matrix, thus playing a role in metal protection and improving the corrosion inhibition efficiency. These results are consistent with the experimental data of the weight loss method used in the above-mentioned experimental examples 2.1-2.4.

[0106] Experimental Example 5

[0107] 0.100 g of lignin ionic liquid composite corrosion inhibitor, lignin, and tetrabutylphosphonium hydroxide benzotriazole ionic liquid were added to 227.3 mL of 5 mol / L HCl hydrochloric acid solution to obtain three BTA-P composite corrosion inhibitors with a concentration of 0.04 wt.%. 4444 -Lig, lignin (Lig), BTA-P 4444 of mixed solution.

[0108] Electrochemical impedance spectroscopy (EIS) was used to evaluate the electrochemical behavior of tetrabutylphosphonium hydroxide benzotriazolium ionic liquid by adding lignin. A traditional three-electrode system was used. The surface exposure area was 1 cm 2 Q235 steel was used as the working electrode, saturated calomel electrode as the reference electrode, and platinum electrode as the auxiliary electrode. The measurement frequency range of electrochemical impedance spectroscopy (EIS) was 10 -2 -10 5 Hz, the AC amplitude was 10 mV. After the open circuit potential was stabilized, the corrosion inhibition performance of Q235 steel immersed in 5 mol / L HCl solution containing different corrosion inhibitors was tested at room temperature. The results are shown in Table 7, which proves that the addition of lignin can enhance the adsorption of tetrabutylphosphonium hydroxide benzotriazolium ionic liquid on the metal surface and increase the corrosion inhibition efficiency.

[0109] Table 7 Electrochemical impedance spectroscopy test of different corrosion inhibitors with a concentration of 0.04wt.% in 5mol / L HCl solution at room temperature

[0110]

[0111] Experimental Example 6

[0112] 0.100 g of lignin ionic liquid composite corrosion inhibitor, lignin, and tetrabutylphosphonium hydroxide benzotriazole ionic liquid were added to 227.3 mL of 5 mol / L HCl hydrochloric acid solution to obtain three BTA-P composite corrosion inhibitors with a concentration of 0.04 wt.%. 4444 -Lig, Lig, BTA-P 4444 of mixed solution.

[0113] Potentiodynamic polarization curves were used to evaluate the electrochemical behavior of tetrabutylphosphonium hydroxide benzotriazolium ionic liquids by adding lignin. The corrosion inhibition performance of Q235 steel immersed in 5 mol / L HCl solution containing different corrosion inhibitors was measured at a scan rate of 1 mV / s in the dynamic potential range of ±600 mV relative to the open circuit potential. The results are shown in Table 8.

[0114] Table 8 Potentiodynamic polarization curves of different corrosion inhibitors with a concentration of 0.04wt.% in 5mol / L HCl solution at room temperature

[0115]

[0116] From the data in Tables 7 and 8, it can be seen that the charge transfer resistance (R) of Q235 steel immersed in 5 mol / L HCl solution containing 0.04 wt.% lignin, tetrabutyl phosphohydroxide benzotriazolium ionic liquid, and lignin ionic liquid composite material is ct ) value is 763.6Ω / cm 2 、2068.0Ω / cm 2 、5133.0Ω / cm 2 . Double layer capacitance (C dl ) were 2.02×10 -6 μF / cm 2 , 1.15×10 -6 μF / cm 2 , 5.43×10 -7 μF / cm 2 . Corrosion current density (I corr ) are 38.08 μm / cm 2 , 25.39μm / cm 2 、6.046μm / cm 2 . Polarization resistance (R p ) are 661Ω / cm 2 、1029.8Ω / cm 2 、5241.6Ω / cm 2 .

[0117] These results show that lignin and tetrabutylphosphonium hydroxide benzotriazolium ionic liquid can exert a synergistic effect, so that the lignin ionic liquid composite material exhibits higher charge transfer resistance and polarization resistance, lower corrosion current density and double layer capacitance, and has excellent corrosion inhibition performance. This is because the lignin ionic liquid composite material can form a protective film with the highest surface coverage on the surface of Q235 steel compared to pure ionic liquid and lignin, effectively reducing the direct contact between the corrosive medium and Q235 steel, and playing a role in metal protection. It proves that the synergistic effect between lignin and tetrabutylphosphonium hydroxide ionic liquid makes the composite material have more excellent corrosion inhibition performance.

[0118] Experimental Example 7

[0119] Molecular dynamics (MD) simulation was used to investigate the 4444 , BTA-P 4444 The adsorption film formed on the metal surface when -Lig is used as a corrosion inhibitor, as well as the density of water in the adsorption film, are simulated and calculated.

[0120] Molecular dynamics (MD) simulations were performed in an isothermal and isochoric (NVT) ensemble using the Gromacs 2018 software package based on the AMBER force field and RESP charges. The size of the simulation box is A three-dimensional periodic boundary condition was used, including the SPC / E water model, 60 corrosion inhibitor molecules, and 500 water molecules. A spherical cutoff of 1.5 nm was used for the summation of van der Waals interactions and short-range Coulomb interactions. The temperature of the system was controlled by using a velocity-reset thermostat, and the system was simulated for 10 nanoseconds at 298 K using a leap frog integrator with a time step of 1.0 femtoseconds. All snapshot images were generated in Visual Molecular Dynamics 1.9.3. The results are shown in Figure 1. Figure 1 and Figure 2 shown.

[0121] in, Figure 1 (a) is BTA-P 4444 Snapshot of a molecule adsorbed on the Fe(110) plane. Figure 1 (a1) is BTA-P 4444 A slice of the simulation box with thickness Figure 1 (b) is BTA-P 4444 -Snapshot of Lig molecule adsorbed on Fe(110) plane, Figure 1 (b1) is BTA-P 4444 -A slice of the Lig simulation box with a thickness of Figure 2 For water molecules in BTA-P 4444 , BTA-P 4444 -Lig density in adsorption film.

[0122] from Figure 1 and Figure 2 It can be seen that BTA-P 4444 -Lig forms a thicker adsorption film on the metal surface than BTA-P 4444 . And by Figure 2 The analysis shows that the closer to the metal substrate, the smaller the density of water molecules in the corrosion inhibitor adsorption film. This shows that the closer to the metal substrate, the denser the corrosion inhibitor adsorption film. The density of water molecules in the middle layer of the corrosion inhibitor adsorption film gradually increases. 4444 Adsorption membrane intermediate diffusion layer The water molecule density at the site increases sharply, which is due to the defects of the adsorption film causing the aggregation of water molecules, thereby increasing the water molecule density. 4444 -Lig adsorption membrane intermediate diffusion layer The water molecule density at the BTA-P4444 The defects in the -Lig adsorption film are smaller than those in BTA-P 4444 Adsorption film. 4444 -Lig has better corrosion inhibition performance as a corrosion inhibitor than BTA-P 4444 .

[0123] Experimental Example 8

[0124] The BTA-P was studied using the CP2K 9.1 software package. 4444 , BTA-P 4444 The adsorption behavior of -Lig on Fe(110) surface, where van der Waals interactions were corrected by DFT-D3 method. Figure 3 shown. Figure 3 (a) is BTA-P 4444 Adsorption behavior on metal surfaces; Figure 3 (b) is BTA-P 4444 -Lig adsorption behavior on metal surfaces.

[0125] pass Figure 3 From the analysis, we can see that BTA-P 4444 -Lig contains lignin, and its surface coverage on the surface of Q235 steel is greater than that of BTA-P 4444 This is due to the fact that BTA-P 4444 The active adsorption sites of the molecule are mainly located on the nitrogen-containing heterocyclic ring of the BTA anion and the phosphorus atom of tetrabutylphosphine hydroxide. Lignin contains a large number of active functional groups such as hydroxyl, carboxyl, and carbonyl, which contain a large number of active adsorption sites. Therefore, BTA-P, which contains rich active elements and functional groups, 4444 -Lig forms an adsorption layer with the atoms on the iron surface through chemical bonds, which is larger than that of BTA-P. 4444 , thereby effectively reducing the direct contact area between the corrosive medium and the metal.

[0126] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. An application of a lignin ionic liquid composite material, characterized in that: The lignin ionic liquid composite material is applied in the field of metal corrosion protection.

2. A method for preparing a lignin ionic liquid composite material, characterized in that: For preparing the lignin ionic liquid composite material according to claim 1, the preparation method comprises the following steps: Preparation of ionic liquid: adding benzotriazole and tetrabutylphosphonium hydroxide into a reactor, reacting for 18-28 hours under nitrogen protection and room temperature to obtain the ionic liquid; Preparation of lignin ionic liquid composite material: Take the ionic liquid and heat it to 50-200° C., add the lignin to the ionic liquid under stirring, and continue stirring until the lignin is dissolved in the ionic liquid to obtain the lignin ionic liquid composite material.

3. The method for preparing the lignin ionic liquid composite material according to claim 2, characterized in that: In the ionic liquid preparation step, the molar ratio of the benzotriazole to the tetrabutylphosphonium hydroxide is 1:

1.

4. The method for preparing the lignin ionic liquid composite material according to claim 2, characterized in that: In the step of preparing the lignin ionic liquid composite material, the lignin is added to the ionic liquid, and the mixture is stirred and mixed for 10-30 minutes to obtain the lignin ionic liquid composite material.

5. The method for preparing the lignin ionic liquid composite material according to claim 2, characterized in that: In the ionic liquid preparation step, the reaction time is 20-25 hours.

6. The method for preparing the lignin ionic liquid composite material according to claim 2, characterized in that: In the step of preparing the lignin ionic liquid composite material, the dissolution temperature of the lignin in the ionic liquid is 90-150°C.

7. The method for preparing the lignin ionic liquid composite material according to claim 2, characterized in that: The ionic liquid preparation step further comprises: After the reaction of the benzotriazole and the tetrabutylphosphonium hydroxide is completed, a reaction solution containing an ionic liquid is obtained, an organic solvent is used to extract the aqueous phase in the reaction solution containing the ionic liquid, and then the organic solvent is removed by vacuum distillation. Finally, anhydrous magnesium sulfate is added for drying, and a light yellow transparent oily liquid is obtained by filtration, which is the ionic liquid.

8. The method for preparing the lignin ionic liquid composite material according to claim 7, characterized in that: The organic solvent is dichloromethane or chloroform.

9. A lignin ionic liquid composite material, characterized in that: The lignin ionic liquid composite material is the lignin ionic liquid composite material according to claim 1, or the lignin ionic liquid composite material obtained by the preparation method according to any one of claims 2 to 8, wherein the lignin ionic liquid composite material consists of lignin and ionic liquid, and the mass fraction of the lignin is 1-5% of the total mass of the lignin ionic liquid composite material.

10. The lignin ionic liquid composite material according to claim 9, characterized in that: The ionic liquid has a structure shown in Formula 1:

Citation Information

Patent Citations

  • Composite ionic liquid as well as preparation method and application thereof

    CN108623823A

  • Ionic liquid lignin lubricating composition as well as preparation method and application thereof

    CN111004669A

  • Anti-corrosion and wear-resistant integrated coating as well as preparation method and application thereof

    CN117986972A